ANALISIS PERBANDINGAN HARGA DAN KUANTITAS PENJUALAN BUAH IMPOR DAN LOKAL DI KOTA SEMARANG - Parju Parju; Nurchayati Nurchayati (Serat Acitya, 2019)
The purpose of this study is to find out the comparison of the prices of imported and lokal fruits at the city of Semarang and to compare the quantity of sales of imported and lokal fruits in the city of Semarang. The population of the study were all fruit traders in the city of Semarang. The sample in this study were 89 fruit traders in the city of Semarang.The results of the study Price of wine, apples, papaya, melon, durian, srikaya, pear, oranges, lokal kelengkeng and imports are the same, depending on the quality of lokal and imported fruit. Lokal and imported fruits of low quality are sold at low prices, relatively the same, while lokal and imported fruits that are of good quality are sold at higher prices which are relatively the same, so that lokal fruits can be priced to compete with imported fruit. The sales quantity for lecil wine outlets, lokal apples is greater than the sale of imported fruit and the quantity of sales of papaya, melon, durian, lokal kelengkeng orange is lower than imports. While the large dioulette from the sale of grapes, apples, papaya, melon, durian, srikaya, and lokal kelengkeng is lower.Keywords: Price, Sales, Imported Fruits, Lokal Fruits